A systematic review on bilingualism and language processing from 2015-2019 - Soh, Or-Kan; Hazita Azman,; Ho, Su Mei (Penerbit Universiti Kebangsaan Malaysia, 2020)
Over the past few decades, research on bilingualism has been extensively covered but still leaves room for much to be discovered especially in the context of language processing. There is a lack in systematic review on studies that examine the trends, effects, methodological approaches, challenges and limitations on bilingualism in relation to language processing. Therefore, this article aims to offer current understanding on bilingualism and language processing through a process of a critical analysis and synthesis. A total of 20 articles published from 2015-2019 in peer-reviewed journals both abroad and locally were selected to be included in this review for content analysis. Hence, this paper attempts to give a systematic report on the findings categorized by trends, effects, methodological approaches, challenges and limitations. Few main findings emerged: (a) An increasing trend in the study on internal language processing and individual factors affecting bilingualism; (b) The existence of inconsistent effects; (c) The need to re-evaluate methodological approaches; and (d) The lack of research conducted in Malaysia. This review also provides suggestions and opportunities for future research in bilingualism and language processing.